The European Union, a global nuclear non-proliferation actor? - Herrera, M. (2021 ECPR General Conference, 2021)
The EU has attempted to expand its norms and vision of non-proliferation to all members of the international community. However, EU Member States have totally divergent views on these matters. Reality is that nuclear non-proliferation is not an area in which the EU has acted to its full potential. The question that arises is whether third parties regard the European Union as an actor in the field of nuclear non-proliferation. In this context, the acceptance of the norms that the EU aims to expand in this policy area by third parties entails its acceptance as a valid actor. To verify this, we will proceed to conduct two case studies that provide practical evidence of the EU's performance in this policy area: the negotiation of an agreed solution to the issue of Iran's nuclear programme, and the development and deepening of bilateral relations between India and the EU in this policy area. Ultimately, this will enable us to ascertain the EU's real ability to disseminate its norms on nuclear non-proliferation, whether or not the EU's non-proliferation norms have been accepted, and to know to what extent the EU is conceived by other states as a valid player in this policy area.